2017
DOI: 10.1177/0149206316685854
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Effects of Pursuing a Diversification Strategy by Newly Founded Nonprofit Organizations

Abstract: Product diversification is commonly seen as an expansion strategy firms adopt late within their life cycles. In this article, we elucidate the practice of employing a product diversification strategy from inception. We explore the performance effects of product diversification on newly created nonprofit organizations. Our findings suggest that being diversified from the start-up phase is, while detrimental to organizational efficiency, beneficial for organizational survival. We also find that the revenue strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 116 publications
(150 reference statements)
4
44
1
Order By: Relevance
“…In addition, it is interesting to note that SDP practitioners in the current study pursued diversified funding opportunities, given that research has demonstrated that many NGOs prefer to simplify funding streams to enhance organizational autonomy and reduce goal displacement and unpredictability of funding (Khieng & Dahles, 2015). However, other work has demonstrated that diversified funding for newer nonprofits, while decreasing efficiency, may be beneficial for organizational survival (Mendoza-Abarca & Gras, 2017). This latter point is particularly relevant for the current study, as practitioners in newer SDP organizations were the ones who mentioned the importance of diversified funding.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition, it is interesting to note that SDP practitioners in the current study pursued diversified funding opportunities, given that research has demonstrated that many NGOs prefer to simplify funding streams to enhance organizational autonomy and reduce goal displacement and unpredictability of funding (Khieng & Dahles, 2015). However, other work has demonstrated that diversified funding for newer nonprofits, while decreasing efficiency, may be beneficial for organizational survival (Mendoza-Abarca & Gras, 2017). This latter point is particularly relevant for the current study, as practitioners in newer SDP organizations were the ones who mentioned the importance of diversified funding.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Second, diversification strategies can affect new-venture survival and efficiency. Nonprofit new ventures with a broad scope of products/services within and across industries (Tanriverdi & Lee, 2008) had increased chance of survival, vis-à-vis those with a narrow scope, but at the cost of organizational efficiency (Mendoza-Abarca & Gras, 2019). This positive relationship between product diversification and new-venture survival is enhanced for ventures with high revenue diversification, that is, a broad scope of revenue sources for these nonprofit ventures, such as government grants, private donations, and goods sold (Mendoza-Abarca & Gras, 2019).…”
Section: Methods For Systematic Reviewmentioning
confidence: 99%
“…It has been observed that opportunity identification in social enterprises is a result of both discovery and creation and the process of pro-social opportunity identification is influenced by the identity of the social enterprise (Conger et al, 2018;González et al, 2017). Growth is essential for the social enterprises to scale up their social impacts, and hence SE research has tried to understand the barriers to growths of the social enterprises, strategies to overcome those barriers, and the performance implications of diversification growth strategy Mendoza-Abarca & Gras, 2019). Considering that social enterprises have a wide range of stakeholders with diverse interests, stakeholder engagement has been one of the key areas of research in SE .…”
Section: Strategic Aspects Of Social Enterprisesmentioning
confidence: 99%